Pemenuhan Hak Anak di Negara-negara Rumpun Melayu - Mubarok, Nafi' (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2022)
United Nations ratified the Convention on the Rights of the Child in 1089. It is a form of legal protection for children to meet children's rights in UN member countries. As a UN convention, it has coercive power on all UN member states to sign and ratify the Convention. The topic of child rights becomes interesting when the discussion focuses on countries with a long historical culture and civilization. One of them is the Malay civilization, namely Brunei, Indonesia, Malaysia, and Singapore, all are members of the United Nations. This paper presents the finding related to the agreement of the Malay community to the Convention on the Rights of the Child and the follow-up of that agreement in its implementation in the legal system of these countries. At the end of the article, it is concluded that: (1) four countries belonging to the Malay family, Indonesia, Malaysia, Singapore and Brunei, have agreed and ratified the Convention on the Rights of the Child (CRC), but with the application of reservation rights for Malaysia and Brunei; (2) four countries have passed child laws; and (3) the diversity of age limits for children in the four countries. [Pada tahun 1089 Perserikatan Bangsa-bangsa mengesahkannya sebagai Kovensi Hak Anak (Convention of Rights of The Child), yang bentuk perlindungan hukum terhadap anak, sebagai upaya pemenuhan terhadap hak-hak anak di negara-negara anggota PBB. Sebagai konvensi PBB, maka mempunyai kekuatan memaksa pada semua Negara anggota PBB untuk menandatangani dan meratifikasi konvensi tersebut. Menjadi menarik ketika difokuskan pada negara-negara yang mempunyai sejarah panjang, terutama mempunyai kesamaan rumpun dan budaya. Salah satunya adalah negara rumpun Melayu, yaitu Brunei, Indonesia, Malaysia, dan Singapura, yang kesemuanya merupakan anggota PBB. Dalam konteks inilah tulisan ini hadir, yaitu untuk mengetahui persetujuan negara negara rumun Melayu terhadap Konvensi Hak Anak, dan tindak lanjut dari persetujuan tersebut dalam implementasinya dalam system hukum negara-negara tersebut. Di akhir tulisan disimpulkan bahwa: (1) empat negara rumpun Melayu, Indonesia, Malaysia, Singapura dan Brunei, telah menyepakati dan meratifikasi Konvensi Hak Anak (CRC), namun dengan pemberlakuan hak reservasi untuk Malaysia dan Brunei; (2) empat negara telah mengesahkan undang-undang anak; dan (3) adanya keberagaman batasan usia anak di empat negara tersebut.]